TEKNOLOGI ROBOT PERTANIAN PENGUSIR HAMA PEMAKAN BIJI PADI PADA DESA KERTOSARI DAN DESO BANGKALAN KECEMATAN PURWOSARI KABUPATEN PASURUAN - Syahminan . (STMIK YADIKA BANGIL, 2019)
Pests are indeed one of the main enemies of the farmers who can attack plants at any time. One of them that often unsettles farmers is bird pests, not a few farmers are overwhelmed, by continuing to increase bird pests as rice-eating pests. For this reason, when rice seeds are nearing harvest, rice seeds are always unsafe. Pests that feed on worm-seed-eaters are a scourge for farmers about the decline in grain production ... caused by a number of rice-seed-eating animals before harvest. To overcome these problems, some farmers use various methods to keep them from getting attacked by rice-eating animals as they approach the Paneni season. Even the traditional method is always done and becomes the choice for every farmer by making a statue of a farmer in the middle of a rice field to frighten animals who want to eat rice seeds. They are required to guard the rice fields from bird attacks from 6-10 am and 2-6 pm, because these times are a critical time for rice plants to develop knowledge and knowledge to create a tool that can play an important role and can help farmers in order to avoid pests that eat rice seeds Technology is basically made and developed for the needs of facilitating farmers and can replace human tasks. One of them can be applied in the field of agricultural technology and especially rice growers who have great potential in agricultural production.Keywords: robot microcontroller technology in rice plants